2020
DOI: 10.1038/s41598-020-72868-w
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stepwise cerebral hypoperfusion differentially induces synaptic proteome changes in the frontal cortex, occipital cortex, and hippocampus in rats

Abstract: During chronic cerebral hypoperfusion (CCH), the cerebral blood flow gradually decreases, leading to cognitive impairments and neurodegenerative disorders, such as vascular dementia. The reduced oxygenation, energy supply induced metabolic changes, and insufficient neuroplasticity could be reflected in the synaptic proteome. We performed stepwise bilateral common carotid occlusions on rats and studied the synaptic proteome changes of the hippocampus, occipital and frontal cortices. Samples were prepared and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Long-term cerebral hypoperfusion could lead to vascular cognitive impairment, and even stroke. Currently, in preclinical experimental studies, many researchers have explored various animal models to mimic patients’ cerebral hypoperfusion status, including mice, rats and non-human primates’ animal models ( Woodruff et al, 2011 ; Tukacs et al, 2020 ). These models include BCAS model, bilateral common carotid artery occlusion (BCCAO) model, left vertebral artery and bilateral internal carotid artery occlusion (three-vessel occlusion; 3VO) model and others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term cerebral hypoperfusion could lead to vascular cognitive impairment, and even stroke. Currently, in preclinical experimental studies, many researchers have explored various animal models to mimic patients’ cerebral hypoperfusion status, including mice, rats and non-human primates’ animal models ( Woodruff et al, 2011 ; Tukacs et al, 2020 ). These models include BCAS model, bilateral common carotid artery occlusion (BCCAO) model, left vertebral artery and bilateral internal carotid artery occlusion (three-vessel occlusion; 3VO) model and others.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term cerebral hypoperfusion could lead to vascular cognitive impairment, and even stroke. Currently, in preclinical experimental studies, many researchers have explored various animal models to mimic patients' cerebral hypoperfusion status, including mice, rats and non-human primates' animal models (Woodruff et al, 2011;Tukacs et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Stepwise bilateral common carotid artery occlusion was performed on rats as previously described [ 7 , 23 , 24 ]. Briefly, rats were anesthetized with isoflurane (1.5–2% in air), and a ventral midline incision was placed on the neck.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found that the incidence of post-event dementia at 1 year was 34•4% in patients with severe stroke, 8•2% in patients with minor stroke, and 5•2% in patients with transient ischemic attack (Pendlebury and Rothwell, 2019). The underlying mechanism of VaD is still largely unknown but may be associated with pathological processes including chronic hypoperfusion and hypoxia (Tukacs et al, 2020), vascular endothelial dysfunction and damage (Wang et al, 2018), increased blood-brain barrier permeability (Ueno et al, 2019), and oxidative stress and inflammation (Guo et al, 2020;Wang et al, 2020). Therefore, there is a need to elucidate the detailed molecular mechanisms of VaD and explore potential drugs for VaD treatment.…”
Section: Introductionmentioning
confidence: 99%